2014
DOI: 10.1371/journal.pgen.1004733
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Genetic Switch Involving Overlapping Divergent Promoters and DNA Looping Regulates Expression of Conjugation Genes of a Gram-positive Plasmid

Abstract: Plasmid conjugation plays a significant role in the dissemination of antibiotic resistance and pathogenicity determinants. Understanding how conjugation is regulated is important to gain insights into these features. Little is known about regulation of conjugation systems present on plasmids from Gram-positive bacteria. pLS20 is a native conjugative plasmid from the Gram-positive bacterium Bacillus subtilis. Recently the key players that repress and activate pLS20 conjugation have been identified. Here we stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 68 publications
8
51
0
Order By: Relevance
“…Previous work has shown that Rco regulates transcription of the conjugation operon through binding to two operator sites within the intergenic region of rco and the first gene of the conjugation operon, possibly by forming a DNA loop of 75 bp (19). Although we did not observe a preference of the repressor to form tetramers as stated before, we found a DNA binding behavior comparable with that described in the literature (Fig.…”
Section: Rco and Rap Are Homodimers In Solution And Rco Binds To Sevsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous work has shown that Rco regulates transcription of the conjugation operon through binding to two operator sites within the intergenic region of rco and the first gene of the conjugation operon, possibly by forming a DNA loop of 75 bp (19). Although we did not observe a preference of the repressor to form tetramers as stated before, we found a DNA binding behavior comparable with that described in the literature (Fig.…”
Section: Rco and Rap Are Homodimers In Solution And Rco Binds To Sevsupporting
confidence: 89%
“…3, first panel). However, binding affinity was lower in this region compared with binding to the previously described operator binding sites (19) (Fig. 2D), suggesting that the newly identified binding region may act as a secondary repressor binding site.…”
Section: Rco and Rap Are Homodimers In Solution And Rco Binds To Sevmentioning
confidence: 65%
See 2 more Smart Citations
“…Recently, Ramachandran et al. (Ramachandran et al., ) reported the existence of a DNA loop in the conjugative pLS20 plasmid of the soil bacterium Bacillus subtilis . Similar to pCF10, transcriptional regulation of pLS20 major conjugation operon is repressed by the master repressor protein Rco LS20 .…”
Section: Discussionmentioning
confidence: 99%